Anti-icing coatings and wind turbine blades with damping absorption capabilities
By applying an anti-ice coating with damping and absorption capacity to the surface of the equipment, the equipment operation instability and damage caused by ice adhesion and vibration is solved, and stable operation and equipment protection are achieved in cold environments.
Patent Information
- Application Number
- CN202310317894.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-28
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2043-03-28
AI Technical Summary
Equipment operating in cold environments such as wind power blades, hulls and turbine blades of aircraft are prone to increase self-weight and unstable operation due to the adhesion of ice. Long-term vibration and hits in harsh environments will accelerate equipment damage.
An anti-ice coating with damping absorption capacity consists of a damping absorption layer and a hydrophobic layer, which comprises a composite material made of epoxy resin, polyurethane and curing agent, combined with inorganic fillers such as nanosilicon dioxide Particulate, hydrophobic layer uses polymer hydrophobic materials such as fluoropolymers.
This anti-ice coating can not only effectively prevent the surface of the equipment from being frozen, but also absorb and buffer mechanical energy during vibration and strike, reduce equipment damage, reduce maintenance costs, extend service life, and take into account both damping and anti-ice performance.
Smart Images

Figure CN116463027B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of anti-icing technology, and in particular to an anti-icing coating and a fan blade with damping absorption capability. Background Art
[0002] Icing and frosting bring great inconvenience to people's production and life, and will cause huge economic losses, especially for some equipment that needs to operate in cold environments, such as wind turbine blades, ship hulls and aircraft turbine blades. Once there is ice on the surface of the running equipment, it will cause the weight of these equipment to increase sharply, the center of gravity to shift during operation, and the surrounding flow field to change, which will greatly affect the normal operation of the equipment and may even cause equipment damage and lead to serious consequences.
[0003] In addition, mechanical equipment such as fan blades that run continuously for a long time often generate a large amount of vibration mechanical energy, which will not only reduce the energy utilization rate of the mechanical equipment, but also the continuous high-intensity vibration will damage the connection stability of the mechanical equipment and accelerate the wear and tear of parts. The huge noise generated by the vibration will also affect the living environment over a wide range. Moreover, in some harsh environments (such as sandstorms, strong winds, heavy rains and hail), the continuous wind force and the impact of raindrops and ice crystals will also cause damage to the surface of the equipment. Summary of the invention
[0004] In response to the above problems, the present invention provides an anti-icing coating with damping absorption capability and a fan blade having the anti-icing coating. The anti-icing coating has good damping and anti-icing properties, and can solve both the icing problem of mechanical equipment and the problem of easy damage of the equipment during vibration and impact.
[0005] On one hand, the present invention provides an anti-icing coating with damping absorption capability, comprising: a damping absorption layer having a damping absorption material; and a hydrophobic layer formed on the upper surface of the damping absorption layer, wherein the hydrophobic layer comprises at least one or more polymer hydrophobic materials.
[0006] According to this technical solution, polymer hydrophobic materials such as low surface energy polymers can reduce the adhesion of water on the surface of the hydrophobic layer due to the hydrophobic properties of the material itself, thereby inhibiting the crystallization and nucleation of water on the surface of the anti-icing coating, while the damping absorption material can convert the vibration mechanical energy into internal energy through slight deformation of the material, and can form protection on the surface of the equipment, buffering the mechanical vibration of the device itself and the continuous impact of the external environment, thereby reducing the erosion of the substrate by wind, sand and rain, reducing maintenance costs, and extending the service life, while taking into account both damping performance and anti-icing performance.
[0007] As a preferred technical solution, the damping absorption material at least includes a composite material made of epoxy resin, polyurethane and a curing agent, and the molar ratio of the epoxy resin to the polyurethane is 0.6-1.2.
[0008] According to the technical solution, the composite material made of epoxy resin (EP), polyurethane (PU) and curing agent has an interpenetrating polymer network structure (IPN). Due to the mutual penetration between the cross-linked networks, forced mutual dissolution and synergistic effects are generated, so that the damping absorption material has a wider damping temperature range and a higher damping loss factor. In addition, the maximum value of the damping loss factor tanδ of the composite damping absorption material is max The corresponding glass transition temperature T g As the molar ratio of epoxy resin to polyurethane increases, when the molar ratio of epoxy resin to polyurethane is 0.3-1, the maximum value of the damping loss factor tanδ of the damping absorption material obtained is max The corresponding glass transition temperature T g The temperature is -18.4℃~20.7℃, which enables it to have higher damping performance in cold icy environments.
[0009] As a preferred technical solution, the damping and absorbing material also includes inorganic fillers.
[0010] According to the technical solution, the addition of inorganic fillers can increase the interaction between IPN and inorganic fillers, thereby increasing the friction in the material system when the damping and absorbing material undergoes micro-deformation. On a macro scale, the tanδ of the anti-icing coating obtained is max Increased, with better damping performance.
[0011] As a preferred technical solution, the inorganic filler includes fluorosilane-modified nano-silica particles.
[0012] According to this technical solution, fluorosilane-modified nano-silica has a lower surface energy and can be evenly dispersed in the material, promoting the cross-linking reaction of EP and PU and enhancing the intermolecular bond force in the interpenetrating network formed by EP and PU, thereby increasing the toughness of the damping absorption layer and improving the strength of the anti-icing coating.
[0013] As a preferred technical solution, the inorganic filler includes silicon nanosprings or carbon nanosprings.
[0014] According to the technical solution, the addition of nanosprings can greatly improve the damping performance of the damping absorption material. The spiral geometry is more easily entangled with the interpenetrating molecular chains, so that when the vibration interface slips, it can absorb and consume more vibration mechanical energy. The damping absorption performance of the anti-icing coating can achieve buffering of strong winds, heavy rains, hail, etc. on the surface of the equipment, and better reduce the long-term vibration erosion of the coating substrate by wind, sand, heavy rain, etc.
[0015] As a preferred technical solution, the curing agent is a polyamide curing agent or a phenolic modified fatty amine curing agent.
[0016] According to this technical solution, the polyamide curing agent or the phenolic modified fatty amine curing agent is a long-chain flexible curing agent. Compared with the short-chain curing agent and the rigid curing agent, the damping absorption material cured by the long-chain flexible curing agent has a lower crosslinking density and a higher toughness of the crosslinking network, thereby having better damping performance.
[0017] As a preferred technical solution, the polymer hydrophobic material is a fluoropolymer.
[0018] According to the technical solution, fluoropolymers include ethylene-tetrafluoroethylene copolymer (ETFE), polytetrafluoroethylene (PTFE), fluorinated ethylene-propylene copolymer (FEP), perfluoroalkoxy resin (PFA), polychlorotrifluoroethylene (PCTFE), ethylene-chlorotrifluoroethylene copolymer (ECTFE), polyvinylidene fluoride (PVDF), polyvinyl fluoride, perfluorodecyltrimethoxysilane, etc., which have low surface energy and can achieve a stable hydrophobic and anti-icing effect.
[0019] As a preferred technical solution, the hydrophobic layer further includes a micro-nano convex column structure formed by nano-silicon dioxide particles deposited on the upper surface of the hydrophobic layer.
[0020] According to the technical solution, the micro-nano convex column structure is similar to the surface structure of a lotus leaf, with a contact angle with water droplets >150°, and has super hydrophobic properties, further enhancing the hydrophobic and anti-icing properties of the anti-icing coating.
[0021] A second aspect of the present invention further provides a wind turbine blade, which is provided with an anti-icing coating according to any of the above technical solutions. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 is the loss factor tanδ-glass transition temperature T of the damping absorption layer prepared in the embodiment of the present invention g Relationship line chart.
[0023] Figure 2 It is a line graph showing the relationship between the ice sliding angle of the anti-icing coating prepared in an embodiment of the present invention and the ambient temperature.
[0024] Figure 3 It is a line graph showing the relationship between the vibration time and the sliding angle of ice cubes of the anti-icing coating prepared in an embodiment of the present invention. DETAILED DESCRIPTION
[0025] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] An embodiment of the present invention provides an anti-icing coating with damping absorption capability, comprising: a damping absorption layer having a damping absorption material; and a hydrophobic layer formed on the upper surface of the damping absorption layer, wherein the hydrophobic layer comprises at least one or more polymer hydrophobic materials.
[0027] Wherein, the damping absorption material at least includes a composite material made of epoxy resin, polyurethane and a curing agent, the epoxy resin can be a bisphenol A type epoxy resin, which can form a stable inter-polymer network structure (IPN) with polyurethane, and preferably, the molar ratio of epoxy resin to polyurethane is 0.6-1.2. Further, the damping absorption material also includes an inorganic filler. The inorganic filler can be an inorganic nanoparticle or an inorganic nanofiber. Preferably, the inorganic filler includes fluorosilane-modified nano-silica particles, and can also include silicon nanosprings or carbon nanosprings, or can also have fluorosilane-modified nano-silica particles and silicon nanosprings / carbon nanosprings at the same time.
[0028] Preferably, the curing agent for the composite of epoxy resin and polyurethane is a flexible long-chain curing agent, such as a polyamide curing agent or a phenolic modified fatty amine curing agent. The polyamide curing agent or the phenolic modified fatty amine curing agent is a long-chain flexible curing agent. Compared with a short-chain curing agent and a rigid curing agent, the damping absorption material cured by the long-chain flexible curing agent has a lower crosslinking density and a higher toughness of the crosslinking network, thereby having better damping performance.
[0029] In this embodiment, the composite material made of epoxy resin (EP), polyurethane (PU) and curing agent has an interpenetrating polymer network structure (IPN). Due to the mutual penetration between the cross-linked networks, forced mutual dissolution and synergistic effects are generated, so that the damping absorption material has a wider damping temperature range and a higher damping loss factor. In addition, the maximum value of the damping loss factor tanδ of the composite damping absorption material is max The corresponding glass transition temperature T g As the molar ratio of epoxy resin to polyurethane increases, when the molar ratio of epoxy resin to polyurethane is 0.3-1, the maximum value of the damping loss factor tanδ of the damping absorption material obtained is max The corresponding glass transition temperature T gThe temperature of the anti-icing coating is -18.4℃~20.7℃, so that it can have a high damping performance in a cold icy environment, so that even in a cold icy environment, it can stably achieve the effect of reducing the erosion of the substrate by wind, sand and rain. The inorganic filler preferably has a doping mass fraction of 5-20%. The addition of the inorganic filler can increase the interaction between the IPN and the inorganic filler, thereby increasing the friction in the material system when the damping absorption material undergoes micro deformation. On a macro scale, the tanδ of the anti-icing coating prepared is max It is enlarged and has better damping performance, which can absorb and buffer the mechanical vibration energy of wind and rain in more severe stormy weather.
[0030] The modifier of nano-silica can be one or more combinations of perfluorooctyltriethoxysilane, heptadecafluorotrimethoxyethoxysilane, heptadecafluorodecyltrimethoxysilane, pentafluorophenyldimethylchlorosilane and dodecafluoroheptylpropyltrimethoxysilane.
[0031] Preferably, in the hydrophobic layer of the anti-icing coating, the polymer hydrophobic material is a fluoropolymer, for example, the fluoropolymer may be ethylene-tetrafluoroethylene copolymer (ETFE), polytetrafluoroethylene (PTFE), fluorinated ethylene-propylene copolymer (FEP), perfluoroalkoxy resin (PFA), polychlorotrifluoroethylene (PCTFE), ethylene-chlorotrifluoroethylene copolymer (ECTFE), polyvinylidene fluoride (PVDF), polyvinyl fluoride, perfluorodecyltrimethoxysilane, etc., which have lower surface energy and can achieve a stable hydrophobic and anti-icing effect.
[0032] Further preferably, the hydrophobic layer further comprises a micro-nano convex column structure formed by nano-silicon dioxide particles deposited on the upper surface of the hydrophobic layer.
[0033] In this embodiment, the polymer hydrophobic material, such as a low surface energy polymer, has its own hydrophobic properties, and the micro-nano convex column structure on the surface of the hydrophobic layer is similar to the surface structure of a lotus leaf, and the contact angle with the water droplet is >150°, so that the anti-icing coating has super hydrophobic properties, which can reduce the adhesion of water on the surface of the hydrophobic layer, thereby inhibiting the crystallization and nucleation of water droplets on the surface of the anti-icing coating. The damping absorption material prepared in this embodiment has good damping performance and can have a higher loss factor in a wider temperature range. It can use the slight deformation of the material to convert the vibration mechanical energy into internal energy, which can reduce the resonance amplitude of the surface structure of the device, increase fatigue life and reduce noise. In addition, in some harsh environments (such as sandstorms, strong winds, heavy rains and hail, etc.), it can also form a buffer on the surface of the device against the continuous impact of wind force and raindrops and ice crystals, protect the surface of the device from damage, and achieve a stable anti-icing effect, thereby being able to take into account both damping performance and anti-icing performance.
[0034] The following experiment further demonstrates the anti-icing performance of the anti-icing coating provided by this embodiment.
[0035] 1. Material Preparation
[0036] 1.1 Preparation of damping absorption layer
[0037] Silicate and heptadecafluorotrimethoxyethoxysilane were dissolved in an ethanol solvent at a molar ratio of 50:1, and the solution was added to an ethanol solution containing 25% ammonia water after stirring at room temperature for 15 minutes. The resulting mixed solution was further stirred at room temperature for 15 minutes, and then washed, dried, and ground to obtain fluorosilane-modified silica with a particle size of 26±5 nm. The dehydrated epoxy resin and polyurethane were added in a molar ratio of 0.6:1, 0.8:1, 1:1 and 1.2:1 respectively, and stirred at room temperature for 10 minutes to obtain a mixture. Fluorosilane-modified nano-silica and polyamide were weighed in a mass ratio of mixture: fluorosilane-modified nano-silica: polyamide = 1:0.2:0.5. Fluorosilane-modified nano-silica was first added to the mixture, and ultrasonic dispersion was performed for 30 minutes. Polyamide was then added and ultrasonic dispersion was performed for 10 minutes. The obtained damping absorption layer precursor was applied on a carbon steel sheet with a thickness of 1 mm. After constant temperature curing at 60°C for 1 hour, the damping absorption layer 1, damping absorption layer 2, damping absorption layer 3 and damping absorption layer 4 in this embodiment were obtained.
[0038] Dehydrated epoxy resin and polyurethane are added in a ratio of 0.8:1, stirred at room temperature for 10 minutes to obtain a mixture, and then polyamide is weighed and added in a mass ratio of mixture: polyamide = 1:0.5. After stirring evenly, the precursor is coated on a carbon steel sheet with a thickness of 1 mm. After constant temperature curing at 60°C for 1 hour, the damping absorption layer 5 in this embodiment is obtained.
[0039] Dehydrated epoxy resin and polyurethane are added in a ratio of 0.8:1, and stirred at room temperature for 10 minutes to obtain a mixture. Silicon nanosprings and polyamide are weighed in a mass ratio of mixture: silicon nanospring: polyamide = 1:0.2:0.5. Silicon nanosprings are first added to the mixture, and ultrasonic dispersion is performed for 30 minutes. Polyamide is then added and ultrasonic dispersion is performed for 10 minutes. The obtained damping absorption layer precursor is applied on a carbon steel sheet with a thickness of 1 mm. After constant temperature curing at 60°C for 1 hour, the damping absorption layer 6 in this embodiment is obtained.
[0040] 1.2 Preparation of anti-icing coating
[0041] Perfluorodecyltrimethoxysilane is dissolved in ethanol, and the perfluorodecyltrimethoxysilane alcohol solution is coated on the damping absorption layer 1-6 prepared in 1.1, and then the anti-icing coating 1-6 is obtained after drying, and then nano-SiO2 particles are deposited on the surface of the anti-icing coating 2 to obtain the anti-icing coating 7.
[0042] The perfluorodecyltrimethoxysilanol solution was directly coated on the surface of a carbon steel sheet with a thickness of 1 mm, and then dried to obtain a control sample.
[0043] 2. Material Characterization
[0044] 2.1 Damping performance
[0045] The damping absorption layers 1-6 were clamped in a dynamic thermomechanical analyzer with a test frequency of 1 Hz, a heating rate of 3°C / min, and a temperature range of -30°C to 40°C.
[0046] Figure 1 is the experimentally obtained tanδ-T of the damping absorption layer g A line chart showing the relationship between Figure 1 As shown, the tanδ of the damping absorption layer 1 max is 0.721, tanδ max The corresponding T g is -18.4℃, the damping temperature range of tanδ=0.3 is 29.0℃; the tanδ of the damping absorption layer 2 is max is 0.728, tanδ max The corresponding T g is -8.2℃, the damping temperature range of tanδ=0.3 is 31.8℃; the tanδ of the damping absorption layer 3 is max is 0.738, tanδ max The corresponding T g is 11.8℃, and the damping temperature range of tanδ=0.3 is 34.2℃; the tanδ of the damping absorption layer 4 is max is 0.742, tanδ max The corresponding T g is 20.7℃, the damping temperature range of tanδ=0.3 is 35.9℃; the tanδ of the damping absorption layer 5 is max is 0.694, tanδ max The corresponding T g is -7.86℃, the damping temperature range of tanδ=0.3 is 30.8℃; the tanδ of the damping absorption layer 6 is max is 0.751, tanδ max The corresponding T g It is -7.92℃, and the damping temperature range of tanδ=0.3 is 31.4℃.
[0047] In general, by comparing the damping absorption layers 1-4, it can be seen that as the doping ratio of polyurethane increases, the loss factor tanδ of the damping absorption layer increases. max The glass transition temperature T g The damping temperature range is greatly improved, especially the width of the damping temperature range is greatly improved. Among them, the polyurethane doping amount of 0.8-1.0 can make the damping absorption layer still have good damping performance in a cold icy environment.
[0048] By comparing the damping absorption layers 2, 5, and 6 of the comparative documents, it can be seen that the doping of inorganic fillers such as modified nano-silica and silicon nano-springs can greatly improve the loss factor of the damping absorption layer, thereby making the damping absorption layer more shockproof and sound-insulating. In particular, the silicon nano-springs can entangle with the molecular chains of IPN, effectively improving the frictional internal energy during interface slip of the material, thereby making the prepared damping absorption layer have excellent damping performance.
[0049] 2.2 Hydrophobic properties
[0050] Water droplet adhesion experiment and droplet rebound experiment were carried out on the anti-icing coatings 1-7, and the morphology and adhesion of water droplets on the surface of the anti-icing coating were recorded by video observation.
[0051] In the water droplet adhesion experiment, the static water contact angle and rolling angle of the anti-icing coatings 1-7 can be maintained at about 150° and 10°, especially the static water contact angle of the anti-icing coating 7 is 162° and 3.8°, which has excellent superhydrophobic properties. This is because the surface of the anti-icing coating 7 has a superhydrophobic structure of nano-silicon dioxide deposition, and when a needle is used to contact the water droplets on the surface of the anti-icing coating 1-7, the water droplets are easily carried away by the needle and do not adhere to the coating surface. This shows that the anti-icing coating prepared in this embodiment has good hydrophobic properties.
[0052] In the droplet rebound experiment, when a 5 μL droplet hits the coating surface, the droplet first spreads on the surface and then rebounds quickly, indicating that the anti-icing coatings 1-7 all have good superhydrophobicity. Moreover, when the coating surface is further rinsed with a large water flow, the surface of the anti-icing coatings 1-7 can remain dry, and the water droplets slide freely on the coating surface. The experiment proves that the anti-icing coating provided in this embodiment has good superhydrophobicity and self-cleaning properties.
[0053] 2.3 Anti-icing performance
[0054] The anti-icing coatings 1-7 and the control samples were cooled to 0°C, -10°C, -20°C, and -30°C, respectively. Specifically, two clamping devices are set in the temperature control container, which are clamped on both sides of the anti-icing coating respectively. An electrically connected vibration head and a vibration signal amplifier are set above the anti-icing coating, and the vibration frequency is set to 1Hz. Liquid nitrogen is set below the anti-icing coating for cooling, and the temperature is controlled by adjusting the distance between the clamping device and the liquid nitrogen device. After the clamping device is adjusted to a suitable height, when the temperature on the anti-icing coating is consistent with the ambient temperature, an ice cube of the same size (10mm*10mm*10mm) is placed on it, and the vibration is turned on for 10 minutes, and then the clamping device is controlled to slowly tilt to one side, and the tilt angle of the anti-icing coating when the ice cube slides is recorded as the sliding angle.
[0055] Figure 2 It is a line graph showing the relationship between the ice sliding angle and temperature of different anti-icing coatings. Figure 2 As shown, the sliding angles of the anti-icing coatings 1-7 and the control samples remain basically unchanged at temperatures above 0°C. The sliding angle of the control sample 1 begins to increase at temperatures below -10°C, while the sliding angle of the anti-icing coating provided in this embodiment remains basically unchanged at temperatures below -10°C. Therefore, the anti-icing coating provided in this embodiment has better anti-icing performance than a simple hydrophobic anti-icing coating. Among them, in particular, the sliding angle of the anti-icing coating 1 remains basically unchanged at temperatures above -20°C. This is because the anti-icing coating 1 has a lower glass transition temperature and can maintain high efficiency in converting vibrations into internal energy in a lower temperature environment, melt a small amount of ice on the contact interface of the anti-icing coating surface to form a lubricated interface, and further reduce the adhesion of ice.
[0056] Cool the anti-icing coatings 2, 5, and 6 to -30°C. Specifically, two clamping devices are set in the temperature control container, which are clamped on both sides of the anti-icing coating respectively. An electrically connected vibration head and a vibration signal amplifier are set above the anti-icing coating, and the vibration frequency is set to 1Hz. Liquid nitrogen is set below the anti-icing coating for cooling, and the temperature is controlled by adjusting the distance between the clamping device and the liquid nitrogen device. After adjusting the clamping device to a suitable height, wait until the temperature on the anti-icing coating is consistent with the ambient temperature, place an ice cube of the same size (10mm*10mm*10mm) on it, and turn on the vibration, keep it for 10min, 20min and 30min respectively, then control the clamping device to slowly tilt to one side, and record the tilt angle of the anti-icing coating when the ice cube slides as the sliding angle.
[0057] Figure 3 It is a line graph showing the change of sliding angle of different anti-icing coatings after different vibration times. Figure 3As shown, with the increase of vibration time, the sliding angle of the anti-icing coating gradually decreases, indicating that the anti-icing coating is continuously converting the vibration mechanical energy into internal energy. The internal energy will cause the surface of the anti-icing coating to slightly heat up, so that the anti-icing coating can maintain excellent deicing performance for a long time in a cold environment, thereby improving the anti-icing coating's tolerance to cold environments.
[0058] In other embodiments of the present invention, the present invention also provides a wind turbine blade having the above-mentioned anti-icing coating.
[0059] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. An anti-icing coating with damping absorption capability, applied to a wind turbine blade, characterized in that: include: a damping absorbing layer having a damping absorbing material; A hydrophobic layer, formed on the upper surface of the damping absorption layer, comprising at least one or more polymer hydrophobic materials; The damping absorption material at least comprises a composite material made of epoxy resin, polyurethane and a curing agent, and in the mixture of the epoxy resin and the polyurethane, the molar ratio of the epoxy resin to the polyurethane is 0.8:1; The damping absorption material further comprises an inorganic filler, and the inorganic filler comprises a silicon nanospring; The curing agent is a polyamide curing agent; The mass ratio of the mixture to the silicon nanospring and the polyamide curing agent is 1:0.2:0.
5.
2. The anti-icing coating with damping absorption capability according to claim 1, characterized in that: The macromolecular hydrophobic material is a fluoropolymer.
3. The anti-icing coating with damping absorption capability according to claim 1, characterized in that: The hydrophobic layer also includes a micro-nano convex column structure formed by nano silicon dioxide particles deposited on the upper surface of the hydrophobic layer.
4. A fan blade, characterized in that: The wind turbine blade is provided with an anti-icing coating having damping absorption capability as claimed in any one of claims 1 to 3.
Citation Information
Patent Citations
Preparation method of high-solid content wide-temperature range damping polyurethane aqueous dispersion containing nanofiller
CN103146181A
Damping coating with interpenetrating network (IPN) structure, and preparation method of damping coating
CN107974188A
Anti-Icing Composite
US20160009971A1